2019
DOI: 10.1097/jxx.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and addressing practitioner burnout: Results from an advanced practice registered nurse health and well-being study

Abstract: Background: Numerous nursing and physician studies have reported the effects of workload, environment, and life circumstances contributing to burnout. Effects may include job dissatisfaction, poor quality of life, and associated negative patient outcomes. Although assessing clinician burnout to determine effective interventions has become a topic of great importance, there are minimal studies specific to advanced practice registered nurses (APRNs). Purpose: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…In this group, perhaps as in others, there is evidence that this state may lead to other clinical cases including depressive episodes [19,38,41,45,48] and suicide [7,42,49] and into experiencing professional life as negative [33]. Yet there are also various negative consequences [50] to the quality of patient care [43] including the dissatisfaction of patients [51,52] poor working environment that impairs teamwork, increased medical errors [3,5,53] increased post-discharge recovery time [6] increased hospital readmissions [40] more medical-legal disputes, reduced adherence to therapy [54] loss of empathy [48,55] and, as above, medically justified leaves [56]. Given the possibility of suicide, some risk factors [48] such as substance abuse, untreated depression and active suicidal ideation should be taken into consideration.…”
Section: Introductionmentioning
confidence: 52%
“…In this group, perhaps as in others, there is evidence that this state may lead to other clinical cases including depressive episodes [19,38,41,45,48] and suicide [7,42,49] and into experiencing professional life as negative [33]. Yet there are also various negative consequences [50] to the quality of patient care [43] including the dissatisfaction of patients [51,52] poor working environment that impairs teamwork, increased medical errors [3,5,53] increased post-discharge recovery time [6] increased hospital readmissions [40] more medical-legal disputes, reduced adherence to therapy [54] loss of empathy [48,55] and, as above, medically justified leaves [56]. Given the possibility of suicide, some risk factors [48] such as substance abuse, untreated depression and active suicidal ideation should be taken into consideration.…”
Section: Introductionmentioning
confidence: 52%
“…Throughout the COVID-19 pandemic trajectory, there has been a notable and wide-ranging impact on all oncology team members (Sidebar 2). [32][33][34] In a 2020 national study, 31.7% of PAs across all specialties reported that they worked without necessary personal protection equipment, 3.6% had been infected with COVID-19, and 72.4% were at least somewhat concerned about their health or their family's health. 35 The pandemic has also impacted the wellbeing of PAs.…”
Section: Contribution Of Covid-19 To Stress In Oncology Teamsmentioning
confidence: 99%
“…6 In a 2020 survey to advance practice registered nurses and physician assistants at Vanderbilt University Medical Center, 59.6% of respondents reported that they had experienced or were currently experiencing burnout. 7 As clinicians are key players in the healthcare process, burnout also jeopardizes the well-being of patients, coworkers, and the public health system as a whole. 1,8 Clinicians suffering from burnout risk making medical errors and are more likely to leave their field entirely, which would compromise the quality of patient care, experience and satisfaction with care, increased costs related to errors, and the future of the medical system.…”
Section: Background and Significancementioning
confidence: 99%